Robustness Report on "Commercial Imperialism? Political Influence and Trade during the Cold War", by Daniel Berger, William Easterly, Nathan Nunn and Shanker Satyanath (2013) - Douglas Campbell; Abel Brodeur; Magnus Johannesson; Joseph Kopecky; Lester Lusher; Nikita Tsoy (Institute for Replication (I4R), 2024)
Berger, Easterly, Nunn and Satyanath (2013) find that increased US political influence, arising from Cold War interventions, was used to create a larger export market for American products. They find that after CIA interventions, US imports increased dramatically, and the authors rule out other explanations. We first reproduce all regression tables in Berger et al. (2013), and then test for robustness by controlling for imports from other NATO countries and various forms of US aid, sanctions, by multi-way clustering the errors, and by conducting influential analysis. We find that the impact of CIA interventions on US exports is sensitive to additional controls and omitting outliers, although adding in region*year interactive fixed effects tends to strengthen the results. Overall, we find that the paper's original results are robust with a coefficient in the same direction and significant at 5% in 17% of the robustness checks we ran (although 58% were significant at 10%). We find t/z scores 58% as large as the original study on average.
Keywords: D72; F14; F54; N42; N72; 330; Cold War; Trade; CIA interventions; Globalization and International Relations